2010
DOI: 10.1016/j.jcf.2009.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Patient segregation and aggressive antibiotic eradication therapy can control methicillin-resistant Staphylococcus aureus at large cystic fibrosis centres

Abstract: Strict infection control procedures can control MRSA infection and keep the prevalence low in CF clinics. Eradication is achievable in the majority of patients even when significant time has lapsed from initial isolation. In some instances, up to 3 courses of antibiotics were required to achieve eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 29 publications
3
34
0
2
Order By: Relevance
“…In 2008 the Cystic Fibrosis Trust published a comprehensive report with specific recommendations for the management of MRSA in CF centers including addressing segregation, hygiene and surveillance [7]. Segregation and eradication have been shown to be successful in keeping the prevalence of MRSA infection low [21], and minimize the likelihood of cross-infection. None of the MRSA positive patients under study received eradication treatment, but they did receive standard anti-MRSA treatment (vancomycin intravenously or linezolid orally) when they were hospitalized for any infectious exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008 the Cystic Fibrosis Trust published a comprehensive report with specific recommendations for the management of MRSA in CF centers including addressing segregation, hygiene and surveillance [7]. Segregation and eradication have been shown to be successful in keeping the prevalence of MRSA infection low [21], and minimize the likelihood of cross-infection. None of the MRSA positive patients under study received eradication treatment, but they did receive standard anti-MRSA treatment (vancomycin intravenously or linezolid orally) when they were hospitalized for any infectious exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…Doe and colleagues (41) reported that patient segregation and aggressive antibiotic eradication therapy can achieve eradication in the majority of patients with CF. Numerous antibiotic regimens were used; however, the most successful were those regimens that included two oral antibiotics (one of which was rifampin) and nebulized vancomycin.…”
Section: Methicillin-resistant Staphylococcus Aureusmentioning
confidence: 99%
“…Because MRSA is often found outside of the respiratory tract, an eradication attempt may also include treatment with nasal mupirocin and chlorhexidine or bleach baths. Interestingly, in contrast to P. aeruginosa, there is some evidence that chronic MRSA may be eradicated from the respiratory tract (41). Given that oral antibiotics alone may not be enough to eradicate chronic MRSA, the addition of inhaled antibiotics targeting MRSA also may be considered.…”
Section: Methicillin-resistant Staphylococcus Aureusmentioning
confidence: 99%
“…Initial improvements in care included the introduction of pancreatic enzyme replacement therapy (PERT) in the 1960s and enteric coated enzymes in the early 1980s to treat pancreatic insufficiency in combination with a high calorie, high fat diet. Systemic antibiotic therapy for lung infection, initially for Staphylococcus aureus and subsequently against Gram-negative organisms such as Pseudomonas aeruginosa and the development and use of inhaled antibiotic therapies over successive decades have been important therapeutic developments [4][5][6]. Advances in antibiotic therapy, the introduction of mucolytics including dornase alpha (Pulmozyme), hypertonic saline and more effective methods of airway clearance have contributed to the major therapeutic advances from the 1970s to the current era [7].…”
Section: Introductionmentioning
confidence: 99%